2019
DOI: 10.1371/journal.pone.0218711
|View full text |Cite
|
Sign up to set email alerts
|

Mental health professionals’ views and experiences of antipsychotic reduction and discontinuation

Abstract: Background The widely established treatment for psychosis is long-term antipsychotic medication. However, many people stop taking this treatment, and request other options. There are also growing concerns about adverse effects, but currently no professional guidelines to support reducing or stopping these drugs. The views and experiences of individual mental health professionals around reducing and stopping antipsychotics are therefore crucial in treatment decisions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…On the other hand, families, carers and clinicians may be reluctant to take the risk of having to endure another relapse, and this makes the process of withdrawal even more difficult, since many people report that they benefit from having support from other people when they try to reduce medication. 46,[53][54][55][56][57] Institutional factors Societal and institutional forces are ranged against any strategy that could increase the risk of a relapse of a severe mental disorder. The shortterm costs of someone having a relapse can be high.…”
Section: Relapsementioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, families, carers and clinicians may be reluctant to take the risk of having to endure another relapse, and this makes the process of withdrawal even more difficult, since many people report that they benefit from having support from other people when they try to reduce medication. 46,[53][54][55][56][57] Institutional factors Societal and institutional forces are ranged against any strategy that could increase the risk of a relapse of a severe mental disorder. The shortterm costs of someone having a relapse can be high.…”
Section: Relapsementioning
confidence: 99%
“…Yet others do support patients to reduce or stop neuroleptic treatment when they request it, and even encourage patients to consider this option who have not previously done so. 56 Professionals cite the lack of guidance when surveyed about their attitudes towards deprescribing in general, 51 and a desire to identify those patients who are likely to have a good outcome following antipsychotic reduction or discontinuation. 56 Unfortunately, although some individual studies have identified various patient and treatment characteristics that predict subsequent relapse or functional outcome, 42 meta-analyses have failed to confirm any consistent predictors of relapse.…”
Section: Enhancement Of Personal Resources For Copingmentioning
confidence: 99%
See 3 more Smart Citations